Mediation in criminal cases: comparative legal analysis - Fedorchuk, Martna (KROK, 2021)
The article is devoted to the comparative analysis of mediation in criminal cases in particular countries. The article analyzes the approaches of researchers to the understanding of mediation in criminal cases and restorative justice. The international standards in the field of mediation in criminal cases and restorative justice, which are applied by states and implemented in national legislation, are considered. It has been studied that mediation is a form of restorative justice. It was found that in most countries, mediation in criminal cases was introduced through the implementation of pilot projects, and over time, relevant laws on mediation were adopted or legislation was amended. The current state of development of mediation as restorative justice in Ukraine is analyzed.
Keywords: mediation, restorative justice, mediation in criminal cases, victim-offender mediation